NOTARY’S RESPONSIBILITY ON AGAINST THE LAW IN THE MAKING OF AUTHENTIC AGREEMENT - Mohammed Kirenci (UNISSULA, 2018)
Notary is a public official authorized to make an authentic agreement and the other has the same authority as referred to in the office of the Notary Act. In Article 16 of Notary Act mentioned that one of the tasks Notary is honest and trustworthy in the running position. However, in practice many notaries who called the court to account for the authentic agreement made because it contains elements against the law. Notary actions are not in accordance with the legislation and Notary Code and has caused losses to many parties.